The treachery of authority through Banville and Atwood - Lau, Qian Yu (2015)
John Banville’s The Book of Evidence and Margaret Atwood’s The Handmaid’s Tale explores the rejection of authority on multiple levels. The Book of Evidence delves into the world of Freddie Montgomery, who has committed homicide and is recounting his life. In a strange twist of events, Freddie attempts to steal a painting and is seen by a maid, whom he abducts and murders shortly after. He presents a great detachment towards his reality, showing no regard for universal systems in the real world. Conversely, The Handmaid’s Tale is set in the “Republic of Gilead” (33), which is a Christian theocracy, where citizens are oppressed and endure much brutality. The story centers on Offred, who has become a marginalized citizen under the new rule. She is assigned the role of a handmaid, whose sole purpose of existence is to breed. Despite the two novels’ stark differences, there are many striking similarities, particularly from the exploration and subversion of power and order. The texts negate traditional forms of authority through varying topics, such as governance, morality, writing and truth.